Interstitial-resident memory CD8(+) T cells sustain frontline epithelial memory in the lung - Takamura, Shiki (J Exp Med, 2019)
Populations of CD8(+) lung-resident memory T (T(RM)) cells persist in the interstitium and epithelium (airways) following recovery from respiratory virus infections. While it is clear that CD8(+) T(RM) cells in the airways are dynamically maintained via the continuous recruitment of new cells, there is a vigorous debate about whether tissue-circulating effector memory T (T(EM)) cells are the source of these newly recruited cells. Here we definitively demonstrate that CD8(+) T(RM) cells in the lung airways are not derived from T(EM) cells in the circulation, but are seeded continuously by T(RM) cells from the lung interstitium. This process is driven by CXCR6 that is expressed uniquely on T(RM) cells but not T(EM) cells. We further demonstrate that the lung interstitium CD8(+) T(RM) cell population is also maintained independently of T(EM) cells via a homeostatic proliferation mechanism. Taken together, these data show that lung memory CD8(+) T(RM) cells in the lung interstitium and airways are compartmentally separated from T(EM) cells and clarify the mechanisms underlying their maintenance.